2021
DOI: 10.52786/isu.a.32
|View full text |Cite
|
Sign up to set email alerts
|

A correlation of PI-RADS score and pathological grading outcome post radical prostatectomy: A retrospective review

Abstract: Objective: To investigate the correlation between the PI-RADS score and the pathologic Gleason score in the final pathological grading and to detect risk factors associated with the outcomes. Materials and Methods: Data from January 2017 to September 2019 were reviewed. Inclusion criteria included patients who had undergone standard protocol prostate magnetic resonance imaging (MRI) in King Chulalongkorn Memorial Hospital and underwent radical prostatectomy during the period. Data collected were age, PI-RADS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…13 Pripatnanont et al, in 2021, have concluded that PIRADS 5 was found to be highly associated with Gleason score ≥7 with odds ratio of 6.67. 14 However, Slaoui et al, in 2017, have concluded that PIRADS was not associated with significant difference regarding Gleason score distribution within target. 15 mpMRI has a high specificity, meaning that it has the ability to exclude biopsy in patients which would otherwise yield negative result.…”
Section: Resultsmentioning
confidence: 97%
“…13 Pripatnanont et al, in 2021, have concluded that PIRADS 5 was found to be highly associated with Gleason score ≥7 with odds ratio of 6.67. 14 However, Slaoui et al, in 2017, have concluded that PIRADS was not associated with significant difference regarding Gleason score distribution within target. 15 mpMRI has a high specificity, meaning that it has the ability to exclude biopsy in patients which would otherwise yield negative result.…”
Section: Resultsmentioning
confidence: 97%
“…Secondly, we performed a comparison between mpMRI-US TB and SB but not using prostatectomy specimens to assess the mpMRI detectability; this mpMRI undetectable case might be a false negative. Finally, using SB as a referent test is not reasonable because it lacks accuracy due to low sensitivity and specificity (30). Therefore, we used the SB as a reference method to investigate detection rate, PPV and NPV, given the absence of other ethical specimens.…”
Section: Discussionmentioning
confidence: 99%